2017
DOI: 10.1016/j.palaeo.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global climate in the diversity patterns of middle Miocene rodents from the Madrid Basin (Spain)

Abstract: Remarkable palaeoclimatic global changes have been recorded worldwide during the middle Miocene. The Miocene Climatic Optimum (~16.3 to ~15 Ma), one of the warmest phases since the Eocene, was followed by the stepwise cooling trend of the Middle Miocene Climate Transition (~15 to ~13.7 Ma). The entry into an Earth "Icehouse" climate state took place at the end of the latter (~13.76 Ma) marked by one of the major cooling steps in middle Miocene climate recorded at a global scale (Mi3b event). The Madrid Basin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…8B). This latest MMCO peak is reflected by slight increases in temperature (MAT) and precipitation (MAP) records both globally (Zachos et al 2001), as well as in other European basins (Schneider 1992;Planderová et al 1993;Böhme 2003;Mosbrugger et al 2005;Hernández-Ballarín and Peláez-Campomanes 2017;Holcová et al 2018;Utescher et al 2009Utescher et al , 2021 and the Konin Basin studied here (Słodkowska and Widera 2021;Worobiec et al 2021). In the latter case, the accumulation of the MPLS-1 started at the time of this climatic optimum (~15 Ma) and continued (max.…”
Section: Tectonic and Climatic Changesmentioning
confidence: 64%
See 1 more Smart Citation
“…8B). This latest MMCO peak is reflected by slight increases in temperature (MAT) and precipitation (MAP) records both globally (Zachos et al 2001), as well as in other European basins (Schneider 1992;Planderová et al 1993;Böhme 2003;Mosbrugger et al 2005;Hernández-Ballarín and Peláez-Campomanes 2017;Holcová et al 2018;Utescher et al 2009Utescher et al , 2021 and the Konin Basin studied here (Słodkowska and Widera 2021;Worobiec et al 2021). In the latter case, the accumulation of the MPLS-1 started at the time of this climatic optimum (~15 Ma) and continued (max.…”
Section: Tectonic and Climatic Changesmentioning
confidence: 64%
“…During this time interval, the tectonic activity of the Carpathians was also marked by the climax of vertical and lateral displacements, as well as the development of sedimentary basins in the foreland and back-arc areas, alongside volcanic phenomena (Plašienka et al 1997;Fodor et al 1999;Krzywiec 2001;Golonka 2004;Peryt and Piwocki 2004;Schäfer et al 2005;Oszczypko 2006;Andreucci et al 2013;Wysocka et al 2016;Kováč et al 2007Kováč et al , 2017aWidera et al 2008Widera et al , 2019aJarosiński et al 2009;Mach et al 2013;Jankowski and Margielewski 2015;Jankowski and Wysocka 2019;Šujan et al 2020. On the other hand, climatic changes further enhanced by tectonics have been documented in both fauna (Böhme 2003;Hernández-Ballarín and Peláez-Campomanes 2017;Holcová et al 2018) and flora (Schneider 1992;Planderová et al 1993;Utescher et al 2009Doláková et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…5, Procumbens group). This clade began to diversify 9.73 myr ago (95%: 4.65–16.09), after the occurrence of an important cooling event (middle Miocene Climate Transition ~15 to ~13.7 myr) in large parts of the western Mediterranean Basin (Jimenez‐Moreno et al, 2010; Hernández‐Ballarín & Peláez‐Campomanes, 2017). The extant species of this lineage ( F. baetica , F. fontqueri , F. paphlagonica , and F. procumbens ) currently inhabit moister and fresher environments of high mountains.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the association of NAO variability and rainfall on the Iberian Peninsula and in northern Africa has been the subject of various studies (Zorita et al, 1992;Rodó et al, 1997;Knippertz et al, 2003). The correlation found between the values of NAO indices and rainfall also applies to some places in the current Ebro Depression (Goodess and Jones, 2002;Muñoz-Díaz and Rodrigo, 2004;Hernández-Ballarín and Peláez-Campomanes, 2017). Present-day lakes are widely affected by climate variables, such as air temperature, wind velocity and precipitation (Margalef, 1983), and observations have demonstrated that many physical and biological lake properties are controlled by these parameters on seasonal to decadal scales (Catalan et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%